Otolaryngologist adherence to the AAO‐HNSF Allergic Rhinitis Clinical Practice Guideline. Issue 6 (7th February 2018) - Honeybrook, Adam; Ellison, Matthew; Puscas, Liana; Raynor, Eileen
Abstract : Background: In February 2015, the American Academy of Otolaryngology–Head and Neck Surgery (AAO‐HNSF) published the Allergic Rhinitis Clinical Practice Guideline (AR‐CPG). The objective of this study was to assess otolaryngologists' perception of the accuracy and adherence to the AR‐CPG. Methods: A survey was distributed to fellows of the American Academy of Otolaryngic Allergy and members of the American Academy of Otolaryngology–Head and Neck Surgery Foundation. A total of 601 otolaryngologists responded. The survey evaluated otolaryngologists' demographic data, perception of the accuracy of the guideline, and adherence to the guideline action statements. Results: The majority of respondents were actively practicing (544 [90.5%]), for a duration of 11–30 years (308 [51.2%]), in a private practice setting (387 [64.4%]). The cohort was largely fellowship trained (348 [57.9%]) and had reviewed the guideline (428 [71.2%]). Most respondents perceived the guideline as being correct "a great deal" (295 [69.7%]) and deviated from the guideline "only a little" (302 [71.6%]). High rates of adherence to the strong guideline recommendations were observed. Respondents "always/most of the time" recommended intranasal steroids (581 [97.6%]), and oral antihistamines (439 [74%]) as primary therapy. Otolaryngologists in practice for longer were more likely to deviate from the guideline recommendations by obtaining sinonasal imaging ( p = 0.007) and recommending oral leukotriene receptor antagonists as primary therapy ( p = 0.0001). Conclusion: Overall perception of the correctness of and adherence to the AR‐CPG was high in this cohort. Targeted education resources should be provided to otolaryngologists in practice for longer in efforts to reduce harmful or unnecessary variations in care.